GLM LVI: TINJAUAN OSTEOARKEOLOGIS ATAS SEBUAH RANGKA DARI GILIMANUK - Ashwin Prayudi; Rusyad Adi Suriyanto (Balai Arkeologi Bali, 2018)
This research discuss human remain GLM LVI from Paleometallic sites called Gilimanuk, which located in Bali. The aims of this study is to find abnormalities, diseases, and culturaland habitual influences to the individual using macroscopical analysis from osteoarchaeological perspective. The results from this research shows this individual was female with age at death between 35-40 years old. She is interesting to be discussed because she shown evidence of kneeling and using her index finger extensively when she was alive. Moreover there were some diseases such as dental calculus, dental caries, periodontal, dental abscess, and cultural influences to her remain which are betel chewing and dental modification. Penelitian ini membahas mengenai rangka manusia individu GLM LVI yang berasal dari situs Paleometalik Gilimanuk di Desa Gilimanuk, Bali. Penelitian ini bertujuan untuk melihat penyakit dan pengaruh budaya terhadap rangka, dengan menggunakan metode analisis makroskopis dan pendekatan osteoarkeologis. Individu ini adalah seorang perempuan yang berusia 35 - 40 tahun ketika mati. Karakteristik ekstrimitas bawahnya menunjukkan bahwa individu ini sering melakukan aktivitas berlutut dan secara ekstensif menggunakan jari telunjuk pada masa hidupnya. Analisis patologis menunjukkan adanya beberapa jenis penyakit gigi, antara lain kalkulus, karies, periodontal, dan abses. Selain itu terdapat pengaruh kebudayaan berupa konsumsi pinang dan sirih, dan modifikasi gigi. Kata kunci: Gilimanuk, osteoarkeologi, berlutut, menginang